Plant Diversity in Hmong and Mien Homegardens in Northern Thailand - Kamonnate Srithi (2018)
Plant Diversity in Hmong and Mien Homegardens in Northern Thailand. We surveyed 180 homegardens in three Hmong and three Mien villages in northern Thailand to study their floristic diversity and composition and to understand the impact of forced migration and ecological conditions for the development of the rich homegarden flora. We also looked at the role of culturally important species as carriers of cultural identity. We found 406 species: 341 (99 families) and 270 species (90 families) in Hmong and Mien homegardens, respectively. Five lowland villages had the richest homegarden flora, in part due to the presence of many widespread species. Twenty-two species were widespread in tropical countries and found in most Hmong and Mien homegardens, and 14 additional common species were shared between Hmong and Mien homegardens. Seventeen species were exclusive to Hmong homegardens and eight to Mien homegardens; these we have designated as culturally important species. The presence of culturally important species determines the homegardens' characteristics and reflects the cultural identity related to plant uses of a group. Similarities in floristic composition of the two groups can be attributed to widespread and common species. Floristic variation and diversity in homegardens were strongly related to homegarden geographical location, personal preference, and cultural background of the owners. © 2012 The New York Botanical Garden.